Intraoperative parameters and postoperative follow-up of foam-based intraperitoneal chemotherapy (FBIC) - Khosrawipour, Carolina; Nicpoń, Jakub; Kiełbowicz, Zdzisław; Prządka, Przemysław; Liszka, Bartłomiej; Al-Jundi, Said; Khosrawipour, Veria; Li, Shiri; Lau, Hien; Kulas, Joanna; Diakun, Agata; Kielan, Wojciech; et al. (Frontiers in Pharmacology, 2023)
Background: For decades, intraperitoneal chemotherapy (IPC) has been delivered into the abdominal cavity as a liquid solution. Recently the concept of foam as a carrier-solution for IPC was suggested. This in-vivo swine study aims to evaluate the safety, intraoperative parameters, limitations and postoperative complications of foam-based intraperitoneal chemotherapy (FBIC). Methods: Three 65-day-old swine received FBIC with doxorubicin in a laparoscopy setting. Intraoperative parameters were monitored throughout the procedure and an extensive postoperative laboratory monitoring was conducted for 7 days. At day seven an autopsy was performed for further evaluation. Results: The insufflation of FBIC caused a temporary rise in blood pressure and a simultaneous drop in heart rate. Capnography detected a continuous increase in end-tital CO2 levels. A temporary drop of intraabdominal temperature was noted. Postoperative blood and serum laboratory results did not indicate any organ failure. No indication of intraperitoneal infections was noted and no structural tissue changes were visible in the autopsy. Discussion: The application of FBIC appears to be a feasible approach regarding intraoperative anesthesiology and postoperative surgical management. A lack of postoperative structural changes on the seventh day were a promising sign of safety and biocompatibility. Surgical reintervention would have been possible. To discuss a possible clinical application, further studies are required to investigate long-term safety, pharmacodynamics and the antitumoral potential of FBIC.